Pengaruh Media Sosial Tiktok Terhadap Akhlak Remaja Di Jorong Panta Kecamatan Matur - Suci Khairunnisa; Alfurqan Alfurqan (KOLONI, 2024)
This research is motivated by the widespread emergence of TikTok phenomena in daily life. The current development of social media generally provides ease for its users and should be able to influence the morals of teenagers. This research aims to see the extent of the influence of TikTok social media on the morals of teenagers. This research uses a quantitative method. The research data used is primary, sourced from data collection using a Likert scale instrument distributed via Google Forms. The population of this study consists of teenagers who use the TikTok social media platform in Jorong Panta, Matur District, with a sample size of 55 individuals, selected based on the criteria of teenagers aged 15-18 years. The sampling technique used in this research employs a non-probability sampling method with Purposive Sampling. The data utilized in this study is assisted by Smart-PLS 4.0 software. The research results show that the TikTok social media has a T-statistic value of 156.071 > 1.96, and a P-Value of 0.000 < 0.05, thus it can be stated that TikTok social media has